2002
DOI: 10.1055/s-2002-28444
|View full text |Cite
|
Sign up to set email alerts
|

Kurzfristige Ergebnisse ambulanter vs. stationärer Phase-D-Rehabilitation nach Schlaganfall

Abstract: Fifty stroke patients who had already regained basic ADL-functions were investigated at the beginning and end of either inpatient or outpatient rehabilitation of similar therapeutic intensity in the same institution. For geographic reasons, outpatient treatment could only be offered to a subgroup of patients. Neurological deficits, extended ADL-functions and quality of life (SF-36) were assessed. Patients who chose outpatient rehabilitation exhibited milder neurological deficits and better ADL-function at onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…However, these studies didn’t clarify whether patients in non-PAC groups had undergo any outpatient stroke rehabilitations or additional rehabilitative programs. Few studies had compared inpatient and outpatient stroke rehabilitation and found similar improvements in ADL and life quality in both group, with the outpatient rehabilitative model averaging lasting longer than 8 days [49] . Both outpatient and inpatient rehabilitative models had positive impacts on stroke functional recovery and inpatient PAC model offers an alternative for motivated patients for intensive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies didn’t clarify whether patients in non-PAC groups had undergo any outpatient stroke rehabilitations or additional rehabilitative programs. Few studies had compared inpatient and outpatient stroke rehabilitation and found similar improvements in ADL and life quality in both group, with the outpatient rehabilitative model averaging lasting longer than 8 days [49] . Both outpatient and inpatient rehabilitative models had positive impacts on stroke functional recovery and inpatient PAC model offers an alternative for motivated patients for intensive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Weiterhin wurde der Einfluss der Präferenz der Rehabilitanden für eine der beiden Versorgungsformen (Settingwunsch) sowie seiner Realisierung unter Berücksichtigung weiterer potenzieller Einflussgröûen auf die Reha-Ergebnisse analysiert. Nachdem die kurzfristigen Ergebnisse im Sinne einer Zwischenauswertung bereits vorgestellt worden sind [21], werden nachfolgend die Daten der Katamnese (6 Monate nach Entlassung) im Vergleich zu denen der beiden vorherigen Erhebungszeitpunkte dargestellt.…”
Section: Einleitung Und Untersuchungszielunclassified
“…± Es gibt keine signifikanten Unterschiede in der Wirksamkeit zwischen diesen beiden Versorgungsformen. Dies konnte inzwischen für die Indikationsbereiche Orthopädie [14,16], Kardiologie [17], Neurologie [18,19] und Alkoholabhängigkeit [20] Wenn jedoch in definierten Fällen mit wenigen Therapiezielen Maûnahmen in der skizzierten Form von ¹Reha-Modulenª ausreichend ± und möglicherweise sogar besonders wirksam ± sind, um die individuellen Therapieziele zu erreichen, sollte damit begonnen werden, über eine Erweiterung des Interventionsspektrums der Rehabilitation nachzudenken und entsprechende Modellvorhaben durchzuführen.…”
Section: Schlüsselwörterunclassified